Les abus de pouvoir et de fonction en droit pénal canadien - Jodouin, André (Les Cahiers de droit, 1978)
This paper was originally given at the Congrès Henri Capitant to an audience composed mainly of Continental jurists. It deals with abuse of power in the context both of crime and of criminal process. The relative extension of the concept as a criminal qualification and the clear sanctions provided by the Code are contrasted with the permis-sivity of the law relating to the occurence in the criminal process, of different instances of abuse.